A Meta-Analysis on The Effect of Inquiry Learning Model on Students’ Mathematical Problem-Solving Skills - Ramadhani, Rizki; Juandi, Dadang; Nurlaelah, Elah (Indonesian Journal of Science and Mathematics Education, 2021)
This study examines the effect of the inquiry learning model on the mathematical problem solving ability of students in Indonesia through meta-analysis. This study analyzed seven primary studies that met the inclusion criteria. The effect size index was calculated using the Hedges g equation and statistical analysis using comprehensive meta-analysis (CMA) software. Effect size testing is done by analyzing four characteristics, namely class of study, year of study, and sample size. Based on the results of the analysis using CMA, the inquiry learning model has a moderate effect (0.652) on the overall mathematical problem-solving skills of students. The use of the inquiry learning model is more effectively used in 8th-grade, in the range of 2015-2017 and 2018-2020, the sample size is less than or equal to 30. Thus, it can be seen that the inquiry learning model is useful in improving mathematical problem-solving skills.